Efficient compensation of thermal birefringence of a flash-lamp pumped Nd:YAG laser by a simple but novel method - Mondal, S.; Datta, Sambit; Dey, S.; Bera, S.; Singh, S.; Datta, P. (2011)
A simple but novel technique for eliminating depolarization loss resulting from thermally induced stress birefringence of a flash lamp-pumped free running Nd:YAG laser is reported here. The output characteristics of the beam with minimum depolarization loss have been systematically investigated by testing various resonator configuration, pump repetition rate and pump power for a Nd:YAG rod of 4mm diameter and 65mm length. It is shown that, by a tilted Glan-Taylor polarizer inside a stable cavity optimally reduces depolarization loss upto 8%. © 2011 SPIE.